2017
DOI: 10.1088/1674-1056/26/6/068203
|View full text |Cite
|
Sign up to set email alerts
|

Reversal current observed in micro- and submicro-channel flow under non-continuous DC electric field

Abstract: In practical applications of biochips and bio-sensors, electrokinetic mechanisms are commonly employed to manipulate and analyze the characteristics of single bio-molecules. To accurately and flexibly control the movement of single molecule within micro-/submicro-fluidic channels, the characteristics of current signals at the initial stage of the flow are systematically studied based on a three-electrode system. The current response of micro-/submicro-fluidic channels filled with different electrolyte solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Duan et al found that utilization of this three-electrode system reduces the recovery time in the current response of the detector, and improves the stability of the measurements. [17,18,21] Moreover, this integrated system was fixed in a grounded Faraday cage to shield external electromagnetic interference. The potentiostat could provide external voltages ranging from −10 V to 10 V with an accuracy of 1 µV, which was connected to the electrodes to provide stable and accurate voltage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duan et al found that utilization of this three-electrode system reduces the recovery time in the current response of the detector, and improves the stability of the measurements. [17,18,21] Moreover, this integrated system was fixed in a grounded Faraday cage to shield external electromagnetic interference. The potentiostat could provide external voltages ranging from −10 V to 10 V with an accuracy of 1 µV, which was connected to the electrodes to provide stable and accurate voltage.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that there are several factors that affect the electrical characteristics of mixed solutions of DNA and metal ions as they pass through a micro-/nanochannel, such as the concentration and PH values of the electrolyte, the material and inner diameter of the micro-/nanochannel, etc. [17][18][19] Further research indicates that the interaction between DNA molecules and metal ions promotes or inhibits the concentration or mobility of the charged particles in the mixed solution, leading to different electrical characteristics, [20] however, how the interaction works remains unclear.…”
Section: Introductionmentioning
confidence: 99%